Learning to labor in high-technology: experiences of overwork in university internships at digital media firms in North America. (4th May 2022) - Cockayne, Daniel
ABSTRACT: Long working hours have become a normal and expected characteristic of employment in many sectors in the Global North. In this paper I examine subjective and affective experiences of overwork that define students' discussions of internships pursued as mandatary aspects of cooperative undergraduate degree programmes. I interviewed current and former students at the University of Waterloo who completed internships at digital media firms, the majority of whom experienced overwork at these firms. Internships are settings in which young people's expectations of employment begin to solidify, while digital media jobs are often considered particularly desirable – evidence of successful employment at the apex of a globalized and competitive labor market. I argue that exploring experiences of overwork shows how and why overwork has been and continues to be normalized, while radical alternatives to overwork (e.g., work refusal and anti-work politics) become hard to imagine and enact.